Pyrrolo[3, 4-c]pyridine-1, 2-dione: a new electron acceptor for electrochromic conjugated polymers. Issue 47 (15th November 2022) - Vo, Tung Phuc; Chua, Ming Hui; Ang, Shi Jun; Chin, Kang Le Osmund; Soo, Xiang Yun Debbie; Png, Zhuang Mao; Tam, Teck Lip Dexter; Zhu, Qiang; Procter, David John; Xu, Jianwei
Abstract : A series of conjugated polymers containing a novel electron acceptor, which is analogous to phthalimide and can be synthesized by Diels Alder reaction between maleimide and 1, 2, 4-triazine, were found to exhibit promising electrochromic properties. Abstract : A new pyrrolo[3, 4- c ]pyridine-1, 2-dione (PPyD) electron acceptor was synthesized via the Diels Alder reaction between N -alkyl maleimide dienophile and 1, 2, 4-triazine moieties. PPyD was subsequently used to construct five donor–acceptor type conjugated polymers, P1–P5, with thiophene-based donors. The electrochromic properties of the five polymers were studied, showing that the polymers exhibit a range of colours from orange to red and magenta in the neutral state, and switch to blue, green, and yellow, upon applying positive voltages. Good optical contrasts of up to 70.5%, fast switching speeds down to 3.2 s and high colouration efficiencies up to 590 C cm −2 were recorded. This work demonstrates the potential of the novel PPyD acceptor as a promising building block for electrochromic conjugated polymers, and probably other organic electronics.